STRATEGI PENGEMBANGAN KUTA LOMBOK SEBAGAI DESTINASI PARIWISATA BERKELANJUTAN - K a n o m, K a n o m (Jurnal Master Pariwisata (JUMPA), 2015)
This article is about development strategy of Kuta Lombok as a sustainable tourism destination. It aims were identifying and analyzing potencies, obstacles, and formulating the strategies and programs. This article applied theory of planning and theory of tourism area life cycle. The data were collected by observation, in–depth interviews, and documentation studies. Data was analyzed by descriptive qualitative method, and analysis of matrix SWOT: Strengths, Weakness, Opportunities, and Threats. Potency of Kuta Lombok as a sustainable tourism destinations are consists of nature and social culture potency. The factors are that become obstacles as such the lack of adequate human resources, management of tourism destination, lack of public awareness in preventing the cleanliness and environmental sustainability, also security and comfort. The article proposes that two grand strategies include strategy of market penetration and development of tourism product.